Simultaneous structural, magnetic, and electronic transitions in La1-xCaxMnO3 with x=0.25 and 0.50. - Radaelli, P; Cox, D; Marezio, M; Cheong, S; Schiffer, P; Ramirez, A (1995)
The magnetic transitions in La1-xCaxMnO3 (x=0.25, 0.50) were studied by synchrotron x-ray and neutron powder diffraction. For x=0.25 the large V=0.13% at TC is due to the simultaneous insulator-to-metal transition. For x=0.50 below TC we observed a drastic decrease of the b axis and an increase of the a and c axes, due to a Jahn-Teller distortion of MnO6 octahedra. The ferromagnetic transition for x=0.50 is accompanied by an unusual peak broadening terminating at TN. This newly observed behavior can be explained assuming that multiple intermediate phases are simultaneously present in the sample. © 1995 The American Physical Society.